ENERGETICALLY OPTIMAL WORK OF WATER INTAKE STRUCTURES FROM UNDERGROUND SOURCES - I. Yu. Purusova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives Perfecting of the existing schemes of water delivery in the pure tank on a pressure piping and increase in efficiency of submersible pumps on water intaking constructions from underground sources. Discusses the negative manifestations in the operation of water intaking constructions from underground. In the mode of operation of each pump is influenced by external and internal characteristics of the system wells – submersible pump – common culvert – the clean water tank. Methods Mathematical model operation of management process of collaboration of system a water well – a prefabricated conduit with definite forms of boundary conditions. Schemes of an arrangement are shown of water wells and a prefabricated conduit. Results Interference of a duty of certain wells and a prefabricated conduit is studied, unstable work of submersible pumps is defined. The scheme of water delivery is presented to the pure tank on separate pressure pressure lines. To ensure the stability of the pumping equipment, the characteristics of the diameter of the water conduit (its hydraulic resistance) are determined depending on the total hydraulic resistance of the well equipment (well filter, pump, fittings) and the well pipeline. Monitoring of water intake structures allows you to set technical indicators for choosing an independent scheme, to choose the right equipment, taking into account the joint operation of the system borehole - submersible pump - collecting water conduit - RFI. Conclusion Energetically optimal work of water intake structures with separate pressure lines, helps to reduce water losses, while achieving significant savings in electricity. The most favorable for the submersible pump is work on the clean water tank, and not on the prefabricated conduit.